UEFA EURO 2012™ in the Polish Sociopolitical Narration - Michaluk Tomasz; Pezdek Krzysztof (Sciendo, 2015)
Sport constitutes an increasingly popular language of discourse in modern societies, providing a (formal) system of signs, which is easily used by, among others, businesses, media, public persons, and, particularly willingly, politicians. Thus, sport as a system of meanings can transfer any values, being at the same time a pragmatic way of arguing in the practice of social life. An example we analyze, are the events that took place after Poland (and Ukraine) had been chosen to be host countries of UEFA EURO 2012™, as well as those which took place during the tournament itself. In these analyses, we use the concept of semiotics and, in particular, pragmatism as well as Charles Sanders Peirce's triadic sign relation.